Organizing Extracurricular Activities Based on the Arcs Motivation Model: Theory and Practice - Khudoyberdiyeva Shokhsanamxon Mukumjonovna (Scientific Trends, 2026)
This article provides a scientific-theoretical and practical analysis of John Keller's ARCS (Attention, Relevance, Confidence, Satisfaction) motivation model and its application in organizing extracurricular activities. During the research, students examined the four main components of the model—attention, relevance, confidence, and satisfaction—through experimental trials in a school setting. The results of the experimental work on the topic "Higher Purpose" in the 7th grade showed that the ARCS model is an effective tool for enhancing student motivation, ensuring their active participation, and promoting personal development. The article also demonstrates the integration of the model with metacognitive strategies, video content, and hobby-based activities.
Keywords: ARCS model, motivation, extracurricular activities, metacognitive strategies, consolidation, cognitive dissonance, procrastination.